2017
DOI: 10.2527/jas2016.1270
|View full text |Cite
|
Sign up to set email alerts
|

Workload of official contests, net cost of transport, and metabolic power of Mangalarga Marchador horses of marcha batida or picada gaits

Abstract: This study aimed to characterize the maximum heart rate (HR) and the intensity of official marcha contests (OMC) and to compare the cost of transport (COT) and metabolic power (Pmet) of Mangalarga Marchador (MM) horses of marcha batida (MB) and marcha picada (MP) gaits. Twenty-two MM horses participated in this study. The experiment was conducted in 3 phases: 1) maximum effort test (MET), 2) OMC, and 3) standardized marcha test (SMT). To characterize the HR, 19 horses (14 MB and 5 MP) underwent a MET. Of those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Previous studies have shown pacing speeds for MM to vary greatly and be largely individual (Lage et al . 2017). We considered sufficient a movement pattern that was quick, between 12 and 14 km/h, similar to what is seen during competition, especially considering these breeds use mostly aerobic metabolism (Wanderley et al .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown pacing speeds for MM to vary greatly and be largely individual (Lage et al . 2017). We considered sufficient a movement pattern that was quick, between 12 and 14 km/h, similar to what is seen during competition, especially considering these breeds use mostly aerobic metabolism (Wanderley et al .…”
Section: Discussionmentioning
confidence: 99%